Formulasi Sediaan Serum Antioksidan dari Ekstrak Bunga Mawar Merah (Rosa Damascena Mill.) dan Virgin Coconut Oil (VCO) - Wijayati, Nanik (Indonesian Journal of Mathematics and Natural Sciences, 2025)
Free radicals caused by UV rays and pollution can make cell damage that results in aging and skin cancer. This research aims to make a natural antioxidant serum product from rose flower extract (EBM) and virgin coconut oil (VCO) to overcome skin problems caused by free radicals. Antioxidant serum works by stabilizing free radicals. Antioxidant serum from EBM/VCO was tested using DPPH method. The results showed characteristics that EBM has 21.86% yield, contains secondary metabolites of flavonoids, phenols, tannins, saponins, and terpenoids, has a total flavonoid content of 19,994.53 mgQE/g with an IC50 value of 48.63 g/mL. The IC50 value of EBM/VCO antioxidant serum with different ratios are F1 (2:0), F2 (4:0), F3 (6:0), F5 (2:2), F5 (4:2), and F6 (6:2) have IC50 values of 260.12 g/mL, g/mL, 93.21 g/mL, 649.24 g/mL, 587.61g/mL, and 495.67g/mL the highest antioxidant result is F3 with a ratio of 6:0. The results of the physical evaluation of the EBM/VCO antioxidant serum has purple color, distinctive aroma, slightly liquid thick texture, has a spreadability of 5.13 - 9.4 cm, and has a pH of 3.83 -4.31. In this study, the low IC50 value was due to poor VCO quality and low pH due to acidic EBM, it is recommended that further research use VCO with better quality.